2018
DOI: 10.1186/s12902-018-0310-y
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A exposure and type 2 diabetes mellitus risk: a meta-analysis

Abstract: BackgroundThis meta-analytic study explored the relationship between the risk of type 2 diabetes mellitus (T2DM) and bisphenol A concentrations.MethodsThe Embase and Medline (PubMed) databases were searched, using relevant keywords, for studies published between 1980 and 2018. A total of 16 studies, twelve cross-sectional, two case-control and one prospective, were included in the meta-analysis. The odds ratio (OR) and its 95% confidence interval (CI) were determined across the sixteen studies. The OR and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 43 publications
1
45
0
1
Order By: Relevance
“…In a Chinese population case-control study of 251 cases of diabetes mellitus type 2 (DM2) and 251 controls, urinary concentrations of bisphenols (BPAF and BPS) were found to be positively correlated with DM2 [78]. A meta-analysis study determined that BPA toxicity is related to an increased risk of DM2; they reported that both urine and serum BPA levels are positively associated with the risk of DM2 [80]. In a cross-sectional study on the middle-aged and elderly Chinese population, a positive association was found between generalized obesity, abdominal obesity, and insulin resistance [82].…”
Section: Obesity and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Chinese population case-control study of 251 cases of diabetes mellitus type 2 (DM2) and 251 controls, urinary concentrations of bisphenols (BPAF and BPS) were found to be positively correlated with DM2 [78]. A meta-analysis study determined that BPA toxicity is related to an increased risk of DM2; they reported that both urine and serum BPA levels are positively associated with the risk of DM2 [80]. In a cross-sectional study on the middle-aged and elderly Chinese population, a positive association was found between generalized obesity, abdominal obesity, and insulin resistance [82].…”
Section: Obesity and Diabetesmentioning
confidence: 99%
“…Children are more prone to bisphenol exposure, and even low concentrations (≤100 µM) are toxic to brain development in both prenatal and childhood stage [89,[121][122][123][124][125]. Exposure to BPA in the first trimester of pregnancy is associated with sleep-related problems in preschool children [80]. In a longitudinal birth cohort study in California, Harley et al observed that prenatal and early childhood BPA exposure of children results in behavioral problems, including anxiety, depression, and hyperactivity [123].…”
Section: Neurotoxicitymentioning
confidence: 99%
“…In a Chinese population case-control study of 251 cases of diabetes mellitus type 2 (DM2) and 251 controls, urinary concentrations of bisphenols (BPAF and BPS) were found to be positively correlated with DM2 [79]. A meta-analysis study determined that BPA toxicity is related to an increased risk of DM2; they reported that both urine and serum BPA levels are positively associated with the risk of DM2 [81]. In a cross-sectional study on the middle-aged and elderly Chinese population, a positive association was found between generalized obesity, abdominal obesity and insulin resistance [83].…”
Section: Obesity and Diabetesmentioning
confidence: 99%
“…Children are more prone to bisphenol exposure, and even low concentrations (≤ 100 µ M) are toxic to brain development in both prenatal and childhood stage [90,[119][120][121][122][123]. Exposure to BPA in the first trimester of pregnancy is associated with sleep-related problems in preschool children [81]. In a longitudinal birth cohort study in California, Harley et al observed that prenatal and early childhood BPA exposure of children results in behavioral problems, including anxiety, depression, and hyperactivity [121].…”
Section: Neurotoxicitymentioning
confidence: 99%
“…7,8 Furthermore, epidemiological evidence suggest harmful effects such as infertility, lower male sexual function, reduced sperm quality, changes in endogenous sex hormone concentrations, immunotoxicity, obesity, cardiovascular disease, type-2 diabetes, and neurobehavioral problems. [9][10][11] These effects have been identified at human BPA concentrations that lie below safety thresholds of government agencies. These findings, thus, call into question the frequent use of BPA-containing products and bring about concerns of adverse effects from low-dose chronic exposure.…”
Section: Introductionmentioning
confidence: 99%